Answer
t = -4
Step-by-step explanation:
First you subtract 9 from both sides. You get 12 on the right. Then you divide both sides by -3. You get -4.
Answer:
x = 3
Step-by-step explanation:
Given the linear equation :
1/4(x-5)+4=1/3(2x+7)-5/6
(x-5)/4 + 4 = (2x+7)/3 - 5/6
Take the lcm and sum
(x-5+16)/4 = (4x+14-5)/6
(x+11)/4 = (4x+9)/6
Cross multiply
6(x+11) = 4(4x+9)
6x + 66 = 16x + 36
Collect like terms
6x - 16x = 36 - 66
-10x = - 30
x = 30/10
x = 3
Reorder both sides
3y-6x=9
7-4y-3x=9
Multiply both sides
-6x-3y=9
6x+8y=-4
Dived both sides
11y= 5
Y=5/11
Substitute the value of Y
-3x-4(5/11)
Equals —> -14/11
Answer : (5/11 , -14/11)
The answer is B. some of the sample data are missing.
This is because out of the 100 students originally sampled by the government agency, only 88 results were taken.
Additionally, we cannot fully take A. as the answer because a non-response error happens when sampling units are not interviewed maybe because they were unavailable or unwilling. So B. is the safer answer.
Answer:
300 necklaces
Step-by-step explanation:
8,400 divided by 28 equals 300